Prevalence of Salmonella Isolates and Their Distribution Based on Whole-Genome Sequence in a Chicken Slaughterhouse in Jiangsu, China - Gu, Dan; Wang, Zhenyu; Tian, Yuqi; Kang, Xilong; Meng, Chuang; Chen, Xiang; Pan, Zhiming; Jiao, Xinan (Frontiers in Veterinary Science, 2020)
Salmonella has been known as the most important foodborne pathogen, which can infect humans via consuming contaminated food. Chicken meat has been known as an important vehicle to transmit Salmonella by the food supply chain. This study determined the prevalence, antimicrobial resistance, and genetic characteristics of Salmonella at different chicken slaughtering stages in East China. In total, 114 out of 200 (57%) samples were Salmonella positive, while Salmonella contamination was gradually increasing from the scalding and unhairing stage (17.5%) to the subdividing stage (70%) throughout the slaughtering. Whole-genome sequencing (WGS) was then performed to analyze the serotype, antimicrobial resistance gene profiles, and genetic relationship of all Salmonella isolates. The most common serotypes were S. Kentucky (51/114, 44.7%) and S. Enteritidis (37/114, 32.5%), which were distributed throughout the four slaughtering stages, and were also identified in the corresponding environments. The multilocus sequence typing (MLST) analysis revealed that seven sequence types (STs) were occupied by six different serotypes, respectively. Only S. Kentucky had two STs, ST314 was the predominant ST shared by 50 isolates, while the ST198 has 1 isolate. The antimicrobial resistance gene analysis demonstrated that most of the strains belonging to S. Kentucky (39/51, 76.5%) and S. Indiana (15, 100%) contained over five groups of antimicrobial resistance genes. Based on the core genome analysis, 50 S. Kentucky isolates were genetically identical, indicating that one S. Kentucky strain with the same genetic background was prevalent in the chicken slaughtering line. Although 37 S. Enteritidis isolates only had three different antimicrobial resistance gene profiles, the core genome sequence analysis subtyped these S. Enteritidis isolates into five different clusters, which revealed the diverse genetic background of S. Enteritidis in the slaughterhouse. The antimicrobial resistance phenotypes were consistent with the presence of the corresponding resistance genes of S. Kentucky and S. Enteritidis, including tetA, floR, blaTEM-1B, strA/B, sul1/sul2, and gyrA (D87Y). Our study observed a high prevalence of Salmonella in the chicken slaughter line and identified the slaughtering environment as a main source of causing Salmonella cross-contamination during chicken slaughtering. Further studies will be needed to limit the transmission of Salmonella in the slaughterhouse.